Respuesta :

Answer: You have to get rid of the variables (the x's) so subtract 2x from 2x and 11x then go from there.

Step-by-step explanation:

Answer:

3 and 6

Step-by-step explanation:

11x - 53 = x^2 + 2x - 35

Subtract 11x - 53 on both sides,

0 = x^2 + 2x - 35 - ( 11x - 53 )

  = x^2 + 2x - 35 - 11x + 53

  = x^2 + 2x - 11x + 53 - 35

0 = x^2 - 9x + 18

x^2 - 9x + 18 = 0

Now this equation need to factorized.

x^2 - 9x + 18 = 0

x^2 - 3x - 6x + 18 = 0

x ( x - 3 ) - 6 ( x - 3 ) = 0

( x - 3 ) ( x - 6 ) = 0

x - 3 = 0

x = 3

x - 6 = 0

x = 6

The solutions to this system are 3 and 6.